The Dutch Incidence of Infantile Hypertrophic Pyloric Stenosis and the Influence of Seasons - van den Bunder, Fenne A. I. M.; Allema, Jan Hein; Benninga, Marc A.; de Blaauw, Ivo; van de Brug, Tim; den Dulk, Marcel; Hulscher, Jan B. F.; Keyzer-Dekker, Claudia M. G.; Witvliet, Marieke J.; van Heurn, Ernest L. W.; Derikx, Joep P. M. (European Journal of Pediatric Surgery, 2020)
Introduction Studies report contradicting results on the incidence of infantile hypertrophic pyloric stenosis (IHPS) and its association with seasons. We aim to assess the IHPS incidence in the Netherlands and to determine whether seasonal variation is present in a nationwide cohort.Materials and Methods All infants with IHPS hospitalized in the Netherlands between 2007 and 2017 were included in this retrospective cohort study. Incidence rates per 1,000 livebirths (LB) were calculated using total number of LB during the matched month, season, or year, respectively. Seasonal variation based on month of birth and month of surgery was analyzed using linear mixed model and one-way ANOVA, respectively.Results A total of 2,479 infants were included, of which the majority was male (75.9%). Median (interquartile range) age at surgery was 34 (18) days. The average IHPS incidence rate was 1.28 per 1,000 LB (variation: 1.09–1.47 per 1,000 LB). We did not find a conclusive trend over time in IHPS incidence. Differences in incidence between season of birth and season of surgery were not significant (p = 0.677 and p = 0.206, respectively).Conclusion We found an average IHPS incidence of 1.28 per 1,000 LB in the Netherlands. Our results showed no changing trend in incidence and no seasonal variation.
Keywords: hypertrophic pyloric stenosis; infantile hypertrophic pyloric stenosis; incidence; seasonal variation; epidemiology